"Octonauts": Blending in the Names of BBC UK Children’s Programs - Amanda Amalia Noor Arifah; Rio Rini Diah Moehkardi (Lexicon, 2020)
This research investigates the formation process of the blends, the classification, and identify the semantic changes in the names of the BBC UK children’s programs. The methods used in this research are descriptive qualitative, and quantitative. To analyze the formation and classification of the blends, the writer used the theory proposed by Elisa Mattiello. The result shows that morphotactically, the blends are categorized into total and partial blends. Morphonologically, the blends are classified into overlapping and non-overlapping blends. Morphosemantically, the attributive blends are more frequently used than the coordinative blends. Furthermore, there are some semantic changes found in the attributive blends.